The Science Library: Curation and visualization of a science gateway repository. (30th December 2020) - Braines, Dave; Stockdill‐Mander, Jane; Lee, Eunjin
Summary: Scientific publications from a group or consortium often form a coherent larger body of work with underlying threads and relationships. Rich social, structural, and topical networks between authors and organizations can be identified, and to convey these we have created the publicly available "Science Library" as a user‐centric, interactive portal. A key consideration in this endeavor is rapid and efficient curation of the corpus of publications, both in terms of assuring quality, as well minimizing the effort required. For this to be sustainable it must offer substantial benefits to the community and avoid excessive operational cost through cumbersome or complex processes. We describe the agility of the Science Library implementation as a controlled natural language (CNL) semantic knowledge graph and describe the different roles within the community to ensure efficient curation, validation, and provenance of the content. By describing the process of curation and validation, alongside the CNL‐based definition of the model we show how relatively non‐technical users are able to interact with, and contribute to the Science Library. This provides an extensible approach, initially based around digital library and virtual community capabilities, that can be applied more broadly to support other desired capabilities of Science Gateways.